Technically yours [large type] - Williams, Denise, 1982- (Center Point Large Print, 2024)
"Pearl Harris has learned the hard way to be careful in work and in love. She has the chance to make lasting change at OurCode -- a nonprofit aimed at inspiring high schoolers to code -- but a recent scandal puts its reputation at risk. Further complicating things, Pearl didn't expect the one man she never stopped thinking about to join as the newest member of her board of directors. Cord Matthews fell for Pearl when they met in an elevator eight years ago. She's just his type: smart, capable, and makes him laugh, but when she broke his heart, he decided love wasn't for him. When they reconnect after years with no contact, Cord is tempted to consider breaking his ban on serious relationships. But going public with a romance between them might derail Pearl's career and the progress she's made at OurCode. While Pearl and Cord are both hesitant to trust their feelings and take a risk, it soon becomes impossible to keep ignoring the electricity between them. Cord is a skilled programmer, but a workplace romance might spell disaster for both of them -- and love isn't easily debugged."--